PENGARUH COVID-19 TERHADAP KELELAHAN KERJA DI PERUSAHAAN X - Putro, Agnisyah Sutoyo Putro; Susilowati, Indri Hapsari (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2023)
The workers in the PT.X construction project have high work hazards and risks, especially in the face of the COVID-19 pandemic. Because construction projects are projects that must continue, the risk of workers being exposed to COVID-19 is high. If there are workers who are exposed to COVID-19, then directly or indirectly the work carried out by the worker will be replaced/backed up by his co-workers. So this can cause fatigue in construction workers. Work fatigue is one of the causes of work accidents. Fatigue can reduce the concentration of workers, reduce decision-making abilities, reduce work/muscle strength, communication skills, productivity, alertness and physical and mental performance and reduce work motivation. The purpose of this study was to determine the effect of Covid-19 on worker fatigue in the Company. The population in this study were 353 workers at PT.X with inclusion criteria being workers who worked overtime and who replaced their colleagues’ work in the last 1 month and exclusion criteria were workers who never worked overtime and replaced their co-workers as many as 55 workers were analyzed univariately and bivariately with simple linear regression analysis model. The results showed that the COVID-19 pandemic had an effect on fatigue among workers at PT X. A significant variable was the age of workers, who worked > 8 hours a day, length of work > 5 years and less rest time, causing fatigue to worker. Keywords: Covid-19, Fatigue, Workers